Occupational health status among women workers: a study in food industry - VANAJAKSHI, DR. E.; N M, ARADHANA (The journal of contemporary issues in business and government, 2021)
The launch of 'Make in India' and 'Skill India' initiatives envisages establishment of high-class manufacturing facilities and enhancement of skills. Although this will lead to improved manufacturing production, human resources could also be covered by enhancing the occupational health scenario. The present study was conducted to know the level of awareness about occupational health and hygiene among employees and to ascertain impact of occupational health and hygiene on productivity of women employees. Since the study was descriptive in nature hence descriptive research design was adopted to describe the occupational health Status of women employees. 40 samples were drawn from 350 women employees of Neo Foods Private Limited, Tumkur by adopting simple random sampling technique (Lottery method). From this study it was found that, occupational health and hygiene of working women was deteriorated due to not following proper measures in the industry.